Prevalence of Cerebrospinal Fluid Rhinorrhea Following Trans-Sphenoidal Surgery for Pituitary Adenoma in Patients Referred to Loghman Hakim Hospital from 2016 to 2020 - Khoshsirat, Shahrokh; Khajavi, Mahdi; Mousavi Nejad, Seyed Ali; Sharifi, Guive; Rezaei, Omidvar; Samadian, Mohammad; Ebrahimzadeh, Kaveh; Mokhtarinejad, Farhad; Hallajnejad, Mohammad; Peyvandi, Ali Asghar; Bazgir, Narges (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2024)
Background: Endoscopic endonasal transsphenoidal surgery is commonly used to remove pituitary adenomas. However, it can lead to cerebrospinal fluid (CSF) leakage, with an incidence of around 5% in sphenoid transnasal procedures and up to 20% in extended endonasal approaches. A retrospective study was conducted on 160 pituitary adenoma patients admitted to Loghman Hakim Hospital from 2016 to 2020 to evaluate the factors influencing CSF leak. Aim: The aim of this study was evaluating the occurrence of cerebrospinal fluid leakage and analyzing the factors involved. Methods: This is a retrospective analysis of patients diagnosed with pituitary adenoma at Loghman-Hakim hospital over a four-year period. Demographic information, tumor characteristics, surgical procedures, and complications were collected. All patients gave their consent, and the study was approved by the ethics committee. Surgical procedures were conducted using a direct endonasal trans-sphenoidal approach under general anesthesia, and antibiotics were given. Statistical analysis was conducted using SPSS to evaluate the relation between measured variables and the occurrence of CSF leak. Results: The study found that 19.4% of the patients developed CSF leak during their hospital stay. Age and body mass index (BMI) of patients with CSF leak significantly differed from those without. The size of the tumor did not differ significantly between patients with and without CSF leak. The only variable associated with CSF leak was sphenoid sinus anatomy. Conclusion: The study concluded that older patients with a lower BMI and a larger defect size are more prone to CSF leak, but no significant difference was found in tumor size between the groups with and without CSF leak. Sphenoid sinus anatomy correlated with CSF leak, while other factors did not show any correlation with the incidence of CSF leak.